THE EFFECT OF EMPLOYEE NUMBER AND COMPETENCE ON WORKPLACE EFFECTIVENESS, WITH EDUCATION AS A MODERATING VARIABLE FOR EMPLOYEES IN THE TRADE AND CUSTOMER MANAGEMENT DIVISION, AND IN FINANCE, COMMUNICATION, AND GENERAL AFFAIRS AT PT PLN (PERSERO) MAIN DIS - Yasmir Lukman; Kiki Farida Ferine; Sri Rahayu (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the influence of the number of employees and competency on the effectiveness of work results with education as a moderating variable on employees in the Commerce and Customer Management Division and the Finance, Communication and General Division at PT PLN (Persero) North Sumatra Main Distribution Unit. The research problem stems from the importance of the effectiveness of work results in supporting the sustainability of company operations, especially in the electricity distribution sector which demands efficiency, service quality, and accuracy of employee performance. This type of research is quantitative research using a survey method. The population in this study were all employees in the studied field with a sample of 94 respondents determined through saturated sampling techniques. The research instrument was a questionnaire with a Likert scale. Data were analyzed using Partial Least Square (SmartPLS 3.0). The results of the study indicate that: (1) the number of employees has a positive and significant effect on the effectiveness of work results; (2) competency has a positive and significant effect on the effectiveness of work results; (3) education is unable to moderate the relationship between the number of employees and the effectiveness of work results; and (4) education is unable to moderate the relationship between competency and the effectiveness of work results. The R-square value of 0.693 indicates that 69.3% of the variation in work effectiveness can be explained by the number of employees and their competencies, while the remainder is influenced by factors outside the research model. This finding emphasizes the importance of proportionally increasing the number of employees and developing employee competencies in improving work effectiveness. However, the role of education as a moderating variable has not been proven significant in this study.